Chronological approach to the characteristics of Ecuador’s debt with the IMF and the WB [version 2; peer review: 2 approved] - Marcelo Sánchez-Oro Sánchez; Martha Lucía Romero Flores; Ligia Ximena Tapia Hermida; Patricia Alexandra Chiriboga Zamora (F1000Research)
Where did Ecuador’s foreign debt originate and grow to alarming levels? The purpose of this article is to describe, from an analytical perspective based on the contributions of various authors, the origin of Ecuador’s external debt with international institutions such as the World Bank and the International Monetary Fund, as well as the support that these organizations provide for the development of the countries of the South, case Ecuador. To achieve this purpose, a documentary methodology was implemented that included an exhaustive review of studies focused on the specific variables subject to analysis, the PRISMA tool and Atlas.ti 23 were used. The results show that the creation of these financing agencies in their attempt to support the financial stability of developing countries has not been sufficiently effective in improving the welfare conditions of a good percentage of the population and has generated an imbalance in the sustained development of the poorest countries. It is concluded that the capitalist system gives predominant priority to the economic growth of nations, thus relegating in its model the consideration of human development. This orientation does not contribute effectively to the improvement of crucial aspects such: education, health and the standard of living of the population.